Comparison of Fasting Blood Glucose Levels Based on Light Exposure on Glucose Strips Using Point Of Care Testing (POCT) - Lia Mar’atiningsih; Ai Erlinawati; Desy Syswianti; Sabila Afsyaina Arrifa (Jurnal Siti Rufaidah, 2023)
A blood sugar test is an examination procedure performed to determine blood sugar levels in the body. This study entitled "Comparison of Blood Glucose Levels Based on Light Exposure to Glucose Strips Using Point Of Care Testing (POCT)". The research method used is pre-experimental. This study aims to determine the comparison of glucose levels based on exposure to light on glucose strips using POCT. This sample collection was carried out using the Federer formula with a total sample of 16 respondents. The data collection technique in this study was carried out using the Shapiro Wilk normality test and the t-test. Glucose levels examined using glucose strips that were not exposed to sunlight obtained an average value of 87.31 mg/dL. Meanwhile, glucose levels were examined using glucose strips which were exposed to light for 15 minutes and obtained an average value of 108.68 mg/dL. Based on the statistical tests that have been carried out, increased results were obtained on strips that were exposed to sunlight for 15 minutes.